Analytical hierarchy process method for mapping landslide susceptibility to an area along the EW highway (Gerik-Jeli), Malaysia - Tareq H Mezughi, Juhari Mat Akhir, Abdul Ghani Rafek, Ibrahim Ab, . (2012)
In this study, the Analytical Hierarchy Process (AHP) method was used to produce a landslide susceptibility map for an area located in the central northern part of Peninsular Malaysia. The study was carried out using remote sensing data, field surveys, historical data and Geographic Information System (GIS) tool.